Réponses

  • Utilisateur Brainly
2014-05-25T15:41:42+02:00
Bonjour, 

(x-1)^2-4 \\ =x^2-2x+1-4 \\ =x^2-2x-3 \\ =f(x)

Si tu as des questions, n'hésite pas! =)
Comment qu'on trouve -2x ?
c'est comme si tu développais (x - 1)(x - 1) = x^2 - x - x + 1 = x^2 - 2x - 1
2014-05-25T15:41:51+02:00
F(x) = (x-1)²-4 = x²-2*x*1+1²-4
                      = x²-2x+1-4
                      = x²-2x-3
Pourquoi -2*1 ?
car (a-b)² = a²-2*a*b+b² mais comme ici a = x et b = 1 : -2ab = -2*x*1 = -2x
Ah merci ^^
de rien ;)